Redirecting investment for a global food system that is sustainable and promotes healthy diets - Eduardo Bianchi; Catherine Bowyer; J. A. Morrison; Rob Vos; Laura Wellesley (Kiel Institute for the World Economy (IfW), 2018)
More and better quality private sector investment in food systems will be needed if countries are to achieve their Sustainable Development Goals. The key challenge addressed in this paper is how investment in food systems can be redirected such that it is both adequate to drive dynamic food system development and has the quality of promoting inclusive and sustainable systems. Three areas of action are considered: instruments that translate growing consumer awareness of the sustainability aspects of food system development into SDG compliant investment; instruments that encourage investment in food systems in high-risk contexts; and improvements to food system governance. The paper articulates three key areas in which the G20 should take action: (i) to strengthen global platforms for the benchmarking and coordination of private sector sustainability initiatives; (ii) to provide support to the coordinated implementation of voluntary guidelines to foster SDG-compliant investment in higher risk contexts; and (iii) to promote greater coordination between multilateral fora to strengthen the global governance of complex and interlinked food system challenges.
Keywords: P45; Q01; Q18; 330; food systems; investment; voluntary guidelines; sustainable development goals